2005
DOI: 10.1097/01.ccm.0000162491.26292.98
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sufentanil or ketamine administered in target-controlled infusion on the cerebral hemodynamics of severely brain-injured patients*

Abstract: The present study shows that the increase in sufentanil or ketamine plasma concentrations using a target-controlled infusion is not associated with adverse effects on cerebral hemodynamics in patients with severe brain injury. The use of target-controlled infusion could be of interest in the management of severely brain-injured patients. However, there is a need for specific pharmacokinetic models designed for intensive care unit patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(90 citation statements)
references
References 30 publications
1
89
0
Order By: Relevance
“…Two double-blind, randomized, controlled trials compared the effect of prolonged ketamine and sufentanil infusions in the ICU in patients with severe traumatic brain injury postcraniotomy. 19,20 These studies found no differences in mean daily intracranial or cerebral perfusion pressures. Schmittner et al 24 compared the effect of ketamine and fentanyl in patients with severe traumatic brain injuries or aneurysmal subarachnoid hemorrhages and found no significant differences in mean daily intracranial or cerebral perfusion pressures.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Two double-blind, randomized, controlled trials compared the effect of prolonged ketamine and sufentanil infusions in the ICU in patients with severe traumatic brain injury postcraniotomy. 19,20 These studies found no differences in mean daily intracranial or cerebral perfusion pressures. Schmittner et al 24 compared the effect of ketamine and fentanyl in patients with severe traumatic brain injuries or aneurysmal subarachnoid hemorrhages and found no significant differences in mean daily intracranial or cerebral perfusion pressures.…”
Section: Resultsmentioning
confidence: 95%
“…We reviewed the full texts of 192 articles, of which 10 met inclusion criteria. [18][19][20][21][22][23][24][25][26][27] Five randomized trials reported data on 854 patients, [19][20][21]24,25 and 5 prospective controlled studies reported data on 99 patients. 18,22,23,26,27 Tables 1 and 2 CPP, cerebral perfusion pressure.…”
Section: Characteristics Of Retrieved Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Pentobarbital is a GABA agonist, and then the increase in ICP caused by ketamine can be blocked by the use of pentobarbital. In addition, ketamine did not involve a significant change for ICP of severely brain-injured patients [43]. In this study, MCAO site brain could have been severely injured and ketamine may not have increased ICP.…”
Section: Discussionmentioning
confidence: 96%
“…In a more recent randomized study, ketamine-midazolam and sufentanil-midazolam were compared as target controlled infusions and ketamine was found to have no significant change on ICP or CPP [44]. In children, Bar-Joseph and colleagues performed a prospective study where ketamine was administered to control refractory intracranial hypertension.…”
Section: Usd Ketaminementioning
confidence: 98%